Assessing the carbon footprint and climate risk of most consumed food products in Cali, Colombia: Methodological development of a decision support tool - Gerbal, Lisa (International Center for Tropical Agriculture, 2019)
This document is a methodological support complementing the combined methodology proposal. It lists all the steps to be followed to implement it. The initial proposal used Cali as a case study. Nevertheless, this type of methodology can be adapted at different levels: national, regional or other.